EXTH-39. DETECTION, MOLECULAR PROFILING AND CULTURE OF CSF-CTCs IN LEPTOMENINGEAL DISEASE (LMDz) IN MELANOMA TO IMPROVE DIAGNOSIS AND TREATMENT STRATEGIES. (5th November 2018) - Law, Vincent; Evernden, Brittany; Kenchappa, Rajappa; Puskas, John; Ryzhova, Elena; Smalley, Inna; Tran, Nam; Etame, Arnold; Sahebjam, Solmaz; Magliocco, Anthony; Smalley, Keiran; Forsyth, Peter
Abstract: BACKGROUND: Approximately 5% of melanoma-associated brain metastasis also develops universally fatal LMDz. The aim of this study was to improve diagnosis and personalized treatment for melanoma-LMDz by enumerating CTCs from CSF. METHODS: CSF-CTCs were enriched and detected by Veridex CellSearch® System and the circulating melanoma cell kit. Cell-free DNA and cell-associated DNA were extracted, sequenced and profiled. Expanded ex-vivo CSF-CTCs and murine BRAF V600E mutant SM1 cells were labeled with viral fluorophore-NanoLuc BRET and injected into the cisterna magna of immunocomprised mice. These cells were also tested for drug sensitivity in-vitro . RESULTS: CSF-CTCs: 12 patients with definite LMDz and 8 melanoma patients without LMDz were studied. All but 1 LMDz patients (92%) had CSF-CTCs (23 CTCs/ml to 3055 CTCs/ml CSF). In contrast, only 3/8 (37%) melanoma patients without LMDz had CSF-CTCs detected, with significantly lower CTC counts per ml CSF (0.13 CTCs/ml to 0.6 CTCs/ml CSF). CSF-CTCs Profile: LMDz patients showed GNAQ Q209P mutation (uveal melanoma), NRAS Q61R mutation (nasal melanoma) and also BRAF V600E mutation. Ex vivo culture of CSF-CTCs and in-vivo injections : We successfully demonstrated ex-vivo expansion of isolated CSF-CTCs ( 25% of samples). Drug treatment revealed Ceritinib could kill BRAF-inhibitor resistant melanoma-CTCs. Mice injected with SM1-GFP-NanoLuc exhibited tumor growth in 1.5 weeks. Metastasis was detected in the brain and spinal cord regions. CONCLUSIONS: Though current patient size is small, this is the first report of the successful culture and drug testing of CSF-CTCs from patients with LMDz. Single cell analysis and in-vivo testing in progress.